Tool failure modes and wear mechanism of coated carbide tools when drilling Ti-6AI-4V - Rahim, E. A.; Shariff, Safian (InderScience Publishers, 2007)
This paper reports on the performance of TiAlN and Supernitride coated carbide tools when drilling titanium alloy, Ti-6Al-4V. Tool life, tool failure modes and tool wear mechanisms were examined at various cutting speeds of 25, 35, 45 and 55 m/min with a constant feed rate of 0.06 mm/rev. Results showed that Supernitride coated carbide tool outperformed TiAlN coated carbide tool at most cutting speeds investigated. Non-uniform flank wear, excessive chipping and microcracking were the dominant tool failure modes under most tested conditions. Adhesion, attrition and diffusion were the operating wear mechanism on both tools when drilling Ti-6Al-4V